Analisis Kinerja Lightning Arester Pada Jaringan Transmisi 150 kV Sistem Minahasa Khususnya Pada Penyulang Kawangkoan - Lopana - Maruli Ch.M. Barasa; Lily S. Patras; Hans Tumaliang (Universitas Sam Ratulangi, 2017)
Abstract— In the distribution of electrical energy in transmission and distribution networks can not be separated from any interference that can Disrupt the process of distribution of electrical energy, whether it was interference from inside or outside interference. It required protection tools to protect it. It required protection tools to protect it. One of the outside distractions that lead to failure of equipment in the transmission line is a lightning strike. Based on the analysis in 2014, the number of lightning strikes in the transmission network is more or less as much as 95 times.Top protection against lightning strikes on Transmission Network is a lightning rod. Where, for a review analyzing the boarding costs AT 150 kV Transmission Line.Keywords: Boarding cost Analysus, Lightning Arrester, Network Transmission, ProtectionsAbstrak— Didalam penyaluran energi listrik pada jaringan transmisi dan distribusi tidak lepas dari adanya gangguan yang dapat mengganggu proses penyaluran energi listrik, baik itu gangguan dari dalam atau gangguan dari luar. Untuk itu diperlukan alat-alat proteksi untuk memproteksinya. Salah satu gangguan dari luar yang menyebabkan kegagalan pada peralatan di jaringan transimisi yaitu sambaran petir. Berdasarkan hasil analisa pada tahun 2014, jumlah sambaran petir pada jaringan transmisi ini kurang lebih sebanyak 95 kali sambaran. Proteksi utama terhadap sambaran petir pada jaringan transmisi adalah lightning arrester. Dimana, untuk menganalisa kinerja pada jaringan transmisi 150 kV.Kata kunci: Analisis kinerja, Jaringan transmisi, Lightning Arrester, Protektsi.